Analisis Perbandingan Kurikulum 2013 dan Kurikulum Merdeka : Implikasi terhadap Pembelajaran di SD Negeri 067694 Medan Area - Miftahul Jannah; Inggri Lola Amelia; Windy E. Zendrato (Lembaga Pengembangan Kinerja Dosen, 2025)
This study discusses the comparative implementation of the 2013 Curriculum (K13) and the Independent Curriculum in elementary education at UPT SD Negeri 060816. The main focus of this study is to analyze the differences in implementation, identify the challenges and advantages of each curriculum, and evaluate their impact on learning effectiveness. The research method used is observation and interviews with grade 4 and 6 teachers as the main respondents. The results of the study show that the 2013 Curriculum is more structured with complete learning materials, while the Independent Curriculum provides flexibility for teachers and students in the project-based learning process. However, there are significant challenges in the implementation of the Independent Curriculum, including limited learning resources, demands for teacher creativity, minimal parental participation, and difficulties in project-based assessments. However, both curricula have their respective advantages in developing student competencies. This study is expected to contribute to understanding the effectiveness of both curricula at the elementary education level and become a reference for policy makers in improving the quality of learning in schools.